2013
DOI: 10.1002/jgra.50556
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of seismic source as deduced from 1 Hz ionospheric GPS data: Case study of the 2011 Tohoku‐oki event

Abstract: [1] Following the first-time ionospheric imaging of a seismic fault, here we perform a case study on retrieval of parameters of the extended seismic source ruptured during the great M9.0 Tohoku-oki earthquake. Using 1 Hz ionospheric GPS data from the Japanese network of GPS receivers (GEONET) and several GPS satellites, we analyze spatiotemporal characteristics of coseismic ionospheric perturbations and we obtain information on the dimensions and location of the sea surface uplift (seismic source). We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 41 publications
8
87
0
2
Order By: Relevance
“…Ionospheric effects of the Tohoku earthquake are currently the subject of many papers. Above all, it is papers analyzing data from dense networks of GPS-receivers, located on the Asian territory (Akhoondzadeh, 2012;Kakinami et al, 2011;Astafyeva et al, 2013;Hao et al, 2012;Komjathy et al, 2012;Liu, 2012;Occhipinti et al, 2011;Ogawa et al, 2012;Ouzounov et al, 2011;Saito et al, 2011;Tsugawa et al, 2011) and data from the SuperDARN radar, located on the Hokkaido island (Nishitani et al, 2011;Ogawa et al, 2012). These instruments have the best temporal resolution -from several seconds to 2 minutes, enabling to monitor the highly dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric effects of the Tohoku earthquake are currently the subject of many papers. Above all, it is papers analyzing data from dense networks of GPS-receivers, located on the Asian territory (Akhoondzadeh, 2012;Kakinami et al, 2011;Astafyeva et al, 2013;Hao et al, 2012;Komjathy et al, 2012;Liu, 2012;Occhipinti et al, 2011;Ogawa et al, 2012;Ouzounov et al, 2011;Saito et al, 2011;Tsugawa et al, 2011) and data from the SuperDARN radar, located on the Hokkaido island (Nishitani et al, 2011;Ogawa et al, 2012). These instruments have the best temporal resolution -from several seconds to 2 minutes, enabling to monitor the highly dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…During the experiments on detection of ionospheric effects of active influence of Progress CS jet stream, we employed a method of mapping ionospheric disturbances [Perevalova et al, 2008;Tsugawa et al, 2011;Kunitsyn et al, 2011;Perevalova et al, 2012;Afraimovich et al, 2013;Astafyeva et al, 2013]. The method means that for each current moment the position of ionospheric points is plotted on a map for all receiversatellite rays, and the color of points corresponds to the current value of TEC variation amplitude in this ray, which is an indicator of ionospheric disturbances.…”
Section: First Results Of Recording Of Ionospheric Effects In-duced Bmentioning
confidence: 99%
“…The method of mapping ionospheric disturbances, which has been repeatedly used for detecting TIDs [Perevalova et al, 2008;Tsugawa et al, 2011;Kunitsyn et al, 2011;Perevalova et al, 2012;Afraimovich et al, 2013;Astafyeva et al, 2013;Yasyukevich et al, 2015;Zakharov et al, 2016], has demonstrated its effectiveness in detection of local disturbances. We have identified relatively weak and vertically localized disturb-ances caused by the effect of the Progress spacecraft engine in the April 16, 2014 experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is offered to use this kind of observations in tsunami warning systems, and also during monitoring of earth (sea) surface motion in region, which is difficult of access (for example, [1,2]). The principal disadvantage of this method is integrated character of a measurable value of TEC along trajectory of a radio wave (for example, [3]). However, the assumption is accepted that the main contribution to TEC variations appears around the height of the maximum of ionosphere ionization (F2 layer).…”
Section: Introductionmentioning
confidence: 99%